Assessment of Noise Exposure in Operator Cultivator Tiller - MOHAMMAD HOSSEIN BEHESHTI; PARVIZ GHANDHARI (International Journal of Occupational Hygiene, 2015)
Tiller is a hand-tractor is used in Agriculture. The noise emitted from Tiller may affect auditory system of operators seriously. The purpose of this study was to evaluate the noise exposure in operators of this device. In this study, 36 cultivator tillers were examined. Measurement of sound was conducted in different mode using sound level meter model of cell 450 based on ISO 7216 standards. Assessment of noise exposure was performed in state that tiller was in its maximum of working power, but, frequency analysis and determining of dominant frequency was performed in state that Tiller was in the middle of its working power. In the present study, experiments were conducted in three operational conditions i.e. static and neutral mode (idling), land plowing with gear 1 and land plowing with gear 2. Results of this study showed that 8-hour exposure level with noise in 3 different modes is 90, 94.73 and 95.17 dB respectively, which is more than standard. Results of Frequency analysis indicated that in each 3 modes, frequency 2000 was dominant frequency. In addition, the maximum level of exposure was in this frequency. Exposure to noise at frequency of 2000 in neutral mode, land plowing with gear1and gear 2 was respectively 81.30, 86.97, and 88.11 dB. In all measured situations, exposure to noise was higher than the standard limit and there was risk of hearing loss. Thus, further studies and control measures are necessary.